Is postoperative Doppler ultrasonography useful for the early detection of asymptomatic pseudoaneurysm and prevention of haemorrhagic complications after partial nephrectomy?. (29th October 2018) - Nouhaud, François‐Xavier; Williams, Michael; Arnfield, Evyn; Perera, Marlon Lakmal; Cho, Jonathan; Esler, Rachel; Coughlin, Geoff
Abstract : Objective: To assess the clinical utility of systematic Doppler ultrasonography (DUS) after robot‐assisted partial nephrectomy (PN) for the detection of renal artery pseudoaneurysm (PA) and to allow pre‐emptive arterial embolization to reduce the postoperative bleeding risk. Materials and Methods: A retrospective study was conducted including all consecutive patients treated with robot‐assisted PN for renal tumours between 2015 and 2017. Every patient underwent renal DUS in the early postoperative period. The presence of PA, arteriovenous malformation or collection on the DUS, as well as the incidence of haemorrhagic complications and need for transfusion/embolization were assessed. Results: Eighty‐three patients were included, with a median (range) age of 58 (19–80) years. The median (range) follow‐up was 5 (1–30) months. The mean (±sd ) tumour size was 31 (±13.1) mm, the median (range) RENAL nephrometry score was 6 (4–11), and the mean (±sd ) warm ischaemia time was 22 (±7) min. A haemostatic agent was used in 12 patients (14.5%). No patient encountered haemorrhagic complications postoperatively, and no patient required transfusion. The median (interquartile range) time to DUS postoperatively was 7 (6–8) days. DUS revealed one asymptomatic PA (1.2%), which was treated with pre‐emptive embolization. This was the only patient who encountered a Clavien grade III complication, while 20 patients (24%) had a complication grade I/II. Conclusions: No haemorrhagic complications occurred in the present study population, although one asymptomatic PA was found. It was diagnosed early with DUS, allowing pre‐emptive management with embolization. These results suggest the potential clinical utility of early postoperative DUS in order to screen for PA to reduce the risk of post‐PN haemorrhagic complications.